O movimento passional do discurso nas crônicas do cotidiano - Nascimento, Angela do (2007)
This present dissertation is situated in the field of reading, writing and Portuguese Language teaching. Its study theme is the passion movement in speech. It has the Direito à Vaidade from Walcyr Carrasco, as its corpus. The focus of this paper is to identify, in the chronic speech, the usage of rhetoric strategies which can provoke or intensify the passionate speech movement. In order to achieve the proposed goals, three aspects were considered as base for research: Rhetoric, the rhetoric of passions from Aristóteles, and the new rhetoric from Perelman. For the analytic trajectory it was taken into consideration the speech used in the chronic chosen as object of study. The analysis focuses in three basic topics: the social context, that involves a small historic of vain and male behavior considering this aspect; the chronic genre; and the rhetoric analysis, with the ethos formation and the usage of arguments and rhetoric figures. During all the report we can find comments on passion discoveries. The research made it possible to explore the rhetoric strategies used in chronic speech and make more evident the passionate movement that each one of them shows. The obtained results open a way to further investigation not only in the rhetoric field but also in the studies of the passions showed by the speech